Decentralisation in Africa a pathway out of poverty and conflict? - Crawford, Gordon (Amsterdam Amsterdam University, 2008)
The current momentum for decentralization of government in Africa and elsewhere in the developing world is driven in many instances by the needs and desires of donor organizations. This volume questions whether this sort of decentralization offers a significant pathway out of poverty and conflict in Africa?addressing issues of poverty reduction in Uganda, Ghana, Malawi, and Tanzania and issues of conflict management in Mauritius, Namibia, South Africa, Uganda, and Rwanda. Conceptual weaknesses and problems of implementation are addressed, especially the limitations of donor-driven decentralization, in order to illustrate that decentralization is neither the ultimate answer nor a shortcut to the achievement of peace and development in Africa.
Includes bibliographical references and index.
Keywords: Decentralization in government --Africa